Polyadic Constacyclic Codes - Chen, Bocong (2015)
For any given positive integer m, a necessary and sufficient condition for the existence of Type-I m-adic constacyclic codes is given. Further, for any given integer s, a necessary and sufficient condition for s to be a multiplier of a Type-I polyadic constacyclic code is given. As an application, some optimal codes from Type-I polyadic constacyclic codes, including generalized Reed-Solomon codes and alternant MDS codes, are constructed.